Peran Dinas Perpustakaan dan Arsip Kabupaten Karo dalam Meningkatkan Minat Baca Anak yang Terdampak Erupsi Gunung Sinabung - Ginting, Okti Sri Indah Br; Purwaningtyas, Franindya (ARZUSIN, 2024)
This research discusses the role of the Karo Regency Library and Archives Service in increasing interest in reading for children affected by the eruption of Mount Sinabung. This research was conducted with the aim, to find out the role of the Karo Regency Library and Archives Service in increasing reading interest in children affected by the eruption of Mount Sinabung, to find out the role of the library and archives service in socializing libraries to children affected by the eruption of Mount Sinabung, to find out the obstacles faced by the Office of the Republic of Indonesia. Karo Regency Library and Archives in increasing interest in reading for children affected by the eruption of Mount Sinabung. The research method used in this thesis is a descriptive method with a qualitative approach. The data collection technique used is by means of observation, interviews and documentation, while the data analysis technique is carried out in three stages, namely data reduction, data presentation and conclusion drawing. The results of this study are that the role of the Karo Regency Library and Archives Service has been carried out as a public library for children and the community in Karo district, but for children who were affected by the eruption of Mount Sinabung there is not yet. The role of the Karo Regency Library and Archives Service in socializing the Karo Regency Library to children affected by the eruption of Mount Sinabung is still carried out in schools only, however, a special program has not been made for visits to relocation villages. The first obstacle faced by the Karo Regency Library and Archives Service in increasing the reading interest of children affected by the eruption of Mount Sinabung was the first budget, inadequate facilities and low interest in reading.